Use of exome sequencing to determine the full profile of genetic variants in the fluoropyrimidine pathway in colorectal cancer patients affected by severe toxicity. (August 2017) - Pellicer, Marta; García-González, Xandra; García, María I; Blanco, Carolina; García-Alfonso, Pilar; Robles, Luis; Grávalos, Cristina; Rueda, Daniel; Martínez, Joaquín; Pachón, Vanessa; Longo, Federico; Martínez, Virginia; et al.
Aim: To identify genetic variants associated with capecitabine toxicity in fluoropyrimidine pathway genes using exome sequencing.Patients & methods: Exomes from eight capecitabine-treated patients with severe adverse reactions (grade >2), among a population of 319, were sequenced (Ion Proton). SNPs in genes classified as potentially damaging (Sorting Intolerant from Tolerant and Polymorphism Phenotyping v2) were tested for association with toxicity in a validation cohort of 319 capecitabine-treated patients.Results: A total of 17 nonsynonymous genetic variants were identified. Of these, five putative damaging SNPs in DPYD, ABCC4 and MTHFR were genotyped in the validation cohort. DPYD rs1801160 was associated with the risk of toxicity (p = 0.029) and MTHFR rs1801133 with delayed administration of chemotherapy due to toxicity (p = 0.047).Conclusion: Exome sequencing revealed two specific biomarkers of the risk of toxicity to capecitabine.